Analisis tataniaga dan Pilihan Kelembagaan Pemasaran Tembakau di Kabupaten Temanggung = Marketing Analysis and Tobacco Institutions Choice in Temanggung Regency - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The purpose of this research was to find out the market behavior and structure, the margin, the profit sharing, the ratio between profit and marketing costs, farmer's share, the market integration and price transmission elasticity as well as marketing institution choice by farmers analysis. The primary data consisted of 50 farmers in Kledung and Bulu villages and 37 marketing institutions involved in tobacco marketing channel from the farmers up to grader in Temanggung tobacco market. The secondary data was collected from Temanggung government institutions. Data collected was then analysed using margin analysis, price transmission elasticity, ravallion market integration and logistic function model. Results of analysis showed the difference in margin and in the ratio between profit and marketing function cost among marketing institutions. There was a big imbalance in the profit sharing among the marketing institutions. Price received by farmers was relatively small. One percent change in tobacco price in the consumer level has caused a bigger than one percent change in tobacco farmer level, price integration between consumer and producer was observed. The analysis of concentration ratio between the collector traders, the wholesalers and the graders suggested that the market was oligopsony.